2015
DOI: 10.1128/jcm.00239-15
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Subspecies Identification by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: hWe explored the use of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for identification of Fusobacterium nucleatum subspecies. MALDI-TOF MS spectra of five F. nucleatum subspecies (animalis, fusiforme, nucleatum, polymorphum, and vincentii) were analyzed and divided into four distinct clusters, including subsp. animalis, nucleatum, polymorphum, and fusiforme/vincentii. MALDI-TOF MS with the modified SARAMIS database further correctly identified 28 of 34 F. nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Previous studies have demonstrated the significant overabundance of F. nucleatum in colorectal adenomas and cancer. However, it remains unclear how F. nucleatum is involved in the CRC microenvironment (24,25). In the present study, F. nucleatum enhanced the growth and proliferation of NCM460 cells, suggesting that F. nucleatum may contribute to the development of CRC.…”
Section: Discussionmentioning
confidence: 45%
“…Previous studies have demonstrated the significant overabundance of F. nucleatum in colorectal adenomas and cancer. However, it remains unclear how F. nucleatum is involved in the CRC microenvironment (24,25). In the present study, F. nucleatum enhanced the growth and proliferation of NCM460 cells, suggesting that F. nucleatum may contribute to the development of CRC.…”
Section: Discussionmentioning
confidence: 45%
“…in this model, F. nucleatum evolved as a lineage with Fusobacterium periodonticum , and these species share not just a niche but also similar functions that are associated with invasion of host cells. F. nucleatum itself can be further delineated into four subspecies 97 — nucleatum , animalis , vincentii (inclusive of fusiforme ) and polymorphum — although it has been argued that these subspecies are sufficiently divergent at a DNa level as to be considered separate species 9,98 . traditional consideration of these subspecies as largely either commensal ( polymorphum and vincentii ) or disease-associated ( nucleatum and animalis ) merits re-evaluation as fusobacterial isolates from colorectal tumours encompass all of these subspecies 45 (Supplementary table 1).…”
Section: Figmentioning
confidence: 99%
“…F. nucleatum is a human pathogen that is filamentous, Gram-negative, non-spore-forming, nonmotile, and anaerobic [13]. It is a heterogeneous species that belongs to the family Fusobacteriaceae and includes five proposed subspecies ( ss ): ss animalis , ss fusiforme , ss nucleatum , ss polymorphum , and ss vincentii [13, 3941]. Despite the fact that F. nucleatum has been found in various tissues, the most common anatomical site in humans is the oral cavity [13].…”
Section: Porphyromonas Gingivalis and Fusobacterium Nucleatum: Permentioning
confidence: 99%